ANALISIS STRUKTUR KAMUS MONOLINGUAL BAHASA INDONESIA - Teguh Setiawan (Litera, 2013)
This study aims to describe structures, structure types, and structure characteristics of monolingual Indonesian dictionaries. The data sources were four monolingual Indonesian dictionaries, i.e. Kamus Besar Bahasa Indonesia (KBBI), Kamus Pelajar, Kamus Istilah, and Kamus Ilmiah. The data were collected through careful reading and analyzed by means of the content analysis to find out the varied dictionary structures. The findings are as follows. First, the structures of the four dictionaries are different. Of the four dictionaries, only one has a complete structure, namely KBBI. Other dictionaries, namely Kamus Pelajar, Kamus Istilah, and Kamus Ilmiah have only four structures. Second, the structures existing in each dictionary and becoming the core structures are the macro and micro structures. Third, the structure characteristics depend on the dictionary types.